2015
DOI: 10.1016/j.biopsych.2014.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Stress Resilience Through Histone Deacetylase 6–Mediated Regulation of Glucocorticoid Receptor Chaperone Dynamics

Abstract: Background Acetylation of Hsp90 regulates downstream hormone signaling via the glucocorticoid receptor (GR), but the role of this molecular mechanism in stress homeostasis remains poorly understood. We tested whether acetylation of Hsp90 in the brain predicts and modulates the behavioral sequelae of a mouse model of social stress. Methods Mice subjected to chronic social defeat stress (CSDS) were stratified into resilient and vulnerable subpopulations. HPA axis function was probed using a DEX/CRF test. Hsp90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 64 publications
1
43
0
Order By: Relevance
“…Previous studies have found that genetically identical mice that are exposed to this paradigm can be split into separate vulnerable and resilient categories based on the degree of social interaction with other mice following this paradigm (3). In line with the findings of the Yehuda et al (1) article, Jochems et al (2) found that the mice that were vulnerable to CSDS had enhanced GR association with the chaperone protein heat shock protein 90 (Hsp90) and increased translocation of GR to the nucleus in the serotonin neurons of the dorsal raphe (DR). They focused on this region of the brain since previous studies have found that it plays a prominent role in the response to CSDS in mice (4)(5)(6).…”
supporting
confidence: 58%
See 2 more Smart Citations
“…Previous studies have found that genetically identical mice that are exposed to this paradigm can be split into separate vulnerable and resilient categories based on the degree of social interaction with other mice following this paradigm (3). In line with the findings of the Yehuda et al (1) article, Jochems et al (2) found that the mice that were vulnerable to CSDS had enhanced GR association with the chaperone protein heat shock protein 90 (Hsp90) and increased translocation of GR to the nucleus in the serotonin neurons of the dorsal raphe (DR). They focused on this region of the brain since previous studies have found that it plays a prominent role in the response to CSDS in mice (4)(5)(6).…”
supporting
confidence: 58%
“…(1) and Jochems et al (2) in this issue, both studies find an association between glucocorticoid receptor (GR) regulation and the response to traumatic stress. The first finds this association in the development of PTSD in combat veterans and the second in the development of a PTSD-like state in mice following exposure to chronic social defeat stress (CSDS).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…172 Recent studies have found an association between GR regulation and the response to traumatic stress. 173,174 The HDAC6 inhibitor, ACY-738, was shown to increase Hsp90 acetylation in mice, promoting increased incorporation of the FKBP51 cochaperone into Hsp90-GR complexes and causing a suppression of GR function. This led to an enhanced adaptation to stress.…”
Section: Resultsmentioning
confidence: 99%
“…This led to an enhanced adaptation to stress. 174 Thus, through its modulating influences on Hsp90, HDAC6 has been confirmed as a viable therapeutic target for psychosocial stress and depression. The continuing evolution of Hsp90 inhibitory drugs and their relevance to specific diseases hold great promise of exciting developments in the future.…”
Section: Resultsmentioning
confidence: 99%